Smoothing of the time structure of slowly extracted beam from synchrotron by RF-knock-out method - Volochnyuk, A.V.; Dolinskii, A.V.; Bezshyyko, О.A. (Вопросы атомной науки и техники, 2005)
Results of the study are presented in work on smoothing of the time structure of the bunch, slowly extracted from synchrotron. The numerical algorithm has been designed for study of the influence of the radio-frequency field of the resonator on time structure of the bunch. The numerical algorithm is based on method Monte-Carlo, where particles in the beam have been extracted by means a slow moving to the third-order resonance conditions. Characteristics of the time structure are vastly smoothed when synchrotron oscillations have been used as first experiments showed. Theoretical motivation of the reasons, influencing upon time structure of the slowly extracted beam, is explained in given work.